Designing Hollow Brick Waste Based Alkali Activated Composites by Taguchi Method - Mine Kurtay Yıldız (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The use of waste materials in alkali-activated material technologies is important in terms of sustainability. The production of alkali-activated composites (AAC) with hollow brick waste (HBW) as a binder may contribute to solving existing environmental problems related to the depletion of natural resources. In this study, mortars were produced using different concentrations (6 M, 8 M, and 10 M NaOH) and Alkaline Activator/Powder Material (AA/PM) ratios of 0.30, 0.35, and 0.40 through the alkali activation method. The hollow brick waste (HBW) powder was obtained by grinding inactive bricks in brick factories. The prepared mortars were cured separately for each mixture at 90°C for 24 hours. Compressive and flexural strength tests were performed on the prepared perforated hollow brick waste-based composites. The Taguchi method was used to determine the optimum mixing ratios by conducting compressive and flexural strength tests on the produced AAC. To optimize the parameters determined using the Taguchi method, the best mixing ratios were determined using the L9 (3^2) orthogonal index. The compressive and flexural strengths of the mixtures were evaluated considering the signal to noise ratio "larger the better" and the highest compressive strength value was 63.669 MPa and the highest flexural strength value was 6.629 MPa according to the optimum values. According to the obtained results, it was determined that the AAC produced at 6 M NaOH and 0.30 AA/PM ratio exhibited the highest compressive and flexural strength values.